THE INFLUENCE OF AUTOMATIC FLAP GATE ON EROSION IN TIDAL SWAMP AREA - Achmad Syarifudin (Asosiasi Peneliti Sriwijaya, 2022)
This research aims to examine the problem of erosion and sedimentation in canals in swampy areas in South Sumatra, namely the P8-13S scheme of the canal (SPD) Telang I, Banyuasin regency with the influence of flap gate. The research method used is to perform simulations in the laboratory using a scale model and related parameters, such as velocity (v), depth of erosion (de), sedimentation (ds), water density (ρw), gravitation (g), time (t) and distance (x). Dimensional analysis to determine the related parameters that produce a dimensionless parameter relationship model is carried out using the Langhaar method. The result of the study was that the maximum relative erosion (de/t)max occurred at the canals estuary near the flap gate, which was 0.255 during simulation times of 5 minutes. While the maximum relative sedimentation (dd/t)max also occurred at the estuary of the secondary canals (SPD) of 0.05 for 5 minutes. So, the sediment transport process in the secondary canal (SPD) is generally influenced by flow velocity and the presence of a flap gate in the canal to regulate sediment transport.